The costimulatory molecule CD70 is regulated by distinct molecular mechanisms and is associated with overall survival in diffuse large B‐cell lymphoma. Issue 8 (28th May 2013) - Bertrand, P.; Maingonnat, C.; Penther, D.; Guney, S.; Ruminy, P.; Picquenot, J. M.; Mareschal, S.; Alcantara, M.; Bouzelfen, A.; Dubois, S.; Figeac, M.; Bastard, C.; et al.
<x xml:space="preserve">Abstract</x> In diffuse large B‐cell lymphomas (DLBCL), a recurrent deletion of the 19p13 region has recently been described. CD70 and TNFSF9 genes are suspected tumor suppressor genes, but previous studies suggest an oncogenic role for CD70. Therefore, we studied the consequences of variation in CD70 copy number and epigenetic modifications on CD70 expression. Copy‐number variation was investigated in 144 de novo DLBCL tissues by comparative genomic hybridization array and quantitative multiplex PCR. Gene expression was assessed by quantitative RT‐PCR, and CD70 promoter methylation was determined by pyrosequencing. The 19p13.3.2 region was deleted in 21 (14.6%) cases, which allowed the minimal commonly deleted region of 57 Kb that exclusively includes the CD70 gene to be defined. Homozygous deletions were observed in four (2.7%) cases, and acquired single‐nucleotide variations of CD70 were detected in nine (6.3%) cases. CD70 was highly expressed in both germinal centre B‐cell‐like (GCB) and activated B‐cell‐like (ABC) DLBCL compared to normal tissue, with distinct molecular mechanisms of mRNA expression regulation. A gene dosage effect was observed in the GCB subtype, whereas promoter methylation was the predominant mechanism of down regulation in the ABC subtype. However, high CD70 expression levels correlated to shorter overall survival in both the GCB (P = 0.0021) and the ABC (P =0.0158) subtypes. In conclusion, CD70 is targeted by recurrent deletions, somatic mutations and promoter hypermethylation, but its high level of expression is related to an unfavorable outcome, indicating that this molecule may constitute a potential therapeutic target in selected DLBCL. © 2013 Wiley Periodicals, Inc.